Aromaterapi Lavender Untuk Mengurangi Intesitas Mual Muntah Pada Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas Lubuk Alung - Mekar Zenni Radhia; Rahmatul Ulya; Gusmadewi Gusmadewi (Departement of Mathematics Education, 2023)
In the first trimester of pregnancy, expectant mothers may experience nausea and vomiting, known as emesis gravidarum. Nausea and vomiting occur in 60% to 80% of primigravida mothers and 40% to 60% of multigravida mothers. The aim of the study was to determine the effect of lavender aromatherapy on the intensity of nausea and vomiting in pregnant women in the Lubuk Alung Health Center Work Area. The study design was a quasi-experiment with a one-group pretest-posttest design. The population consisted of all pregnant women experiencing nausea and vomiting in the Lubuk Alung Health Center Work Area from June to December 2022, totaling 76 people. The sample for this study consisted of 15 individuals, selected through random sampling. The research instrument used the PUQE Score to assess the intensity of nausea and vomiting in pregnant women. The results showed that lavender aromatherapy had an effect on the intensity of nausea and vomiting in first-trimester pregnant women in the Lubuk Alung Health Center Work Area, with a P-value of 0.000 (P-value < 0.005). It is hoped that first-trimester pregnant women experiencing nausea and vomiting can implement lavender aromatherapy as an effort to reduce these symptoms.